Correction Codes: A Tool for Enhancing Writing Qualities - Thakur, Rameshwar (Journal of NELTA, 2024)
Writing is essential for documenting ideas, feelings and information. Students submit assigned tasks in written forms, which teachers mark for errors using codes to prevent their recurrence in the future. The symbols teachers use to provide written feedback should help improve student writing. However, most students’ fail to understand such symbols. Consequently, they pay less attention to the feedback, and continue to make similar mistakes in their subsequent writings. This qualitative study aimed to explore various forms of codes used by 10 English language teachers teaching in grades 11/12 in diff erent schools in Kavrepalanchok district of Bagmati Province. The study found that students did not understand most of the correction codes used by teachers, nor did they contact the teachers morever for clarifi cation. This lack of interaction hindered the eff ectiveness of these codes in improving writing. Teachers did not orient students about such codes, and most students did not seek help to understand them. It was recommended that the teacher use context-based techniques for scoring and providing written corrective feedback.